Short Communication: Effects of felling intensity on Hymenoptera biodiversity in a natural production forest in East Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2017)
Ahmad B, Haneda NF, Robaikah ID. 2016. Short Communication: Effects of felling intensity on Hymenoptera biodiversity in a natural production forest in East Kalimantan, Indonesia. Biodiversitas 18: xxxx. Hymenoptera is one of the major components of insect biodiversity, where its abundance and diversity contributes to the functioning of the forest ecosystem. Most of the tropical forest in Kalimantan island has been logging since 1970. Tree felling is the initial step of logging activity. This activity leads to change Hymenoptera diversity. This study analyzes the effects of felling intensity on the Hymenoptera diversity in 100 ha area in a natural production forest in East Kalimantan, Indonesia. In this study, the diversity, evenness, and species richness index of Hymenoptera was compared before and after felling in three intensities (low, moderate, and high). Insects were collected in 9 purposively located 0.5 ha plots using a malaise trap. Three malaise traps were set in each plot The results showed that the timber felling tends to decrease the abundance of Hymenoptera. Diversity and species richness of Hymenoptera will decline in moderate and high felling intensity, whereas evenness index of Hymenoptera unchanged at three felling intensities. The composition of morphospecies of Hymenoptera was changed after tree felling with high intensity. The results of the study suggest that minimizing the felling intensity may reduce disruption of insect habitat in natural production forest in East Kalimantan, Indonesia.
Keywords: Biodiversity; felling intensity; Hymenoptera; natural production forest